2020
DOI: 10.3390/ijerph17197013
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Intermediary Role of Perceived Stress in the Relationship between Mindfulness and Burnout Subtypes in a Large Sample of Spanish University Students

Abstract: The burnout syndrome is the consequence of chronic stress that overwhelms an individual’s resources to cope with occupational or academic demands. Frenetic, under-challenged, and worn-out are different burnout subtypes. Mindfulness has been recognized to reduce stress, comprising five facets (observing, describing, acting with awareness, non-judging of inner experience, and non-reactivity to inner experience). This cross-sectional study aimed to assess the relationship between mindfulness facets, perceived str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 83 publications
0
12
0
2
Order By: Relevance
“…Different investigations and bibliographic reviews have shown how higher levels of mindfulness improve mental and physical health, and the quality of relationships with others [47,50,51]. In this vein, the literature highlights seven different core processes as the main ones benefiting from mindfulness in business: attention, awareness, cognition, self-regulation of behavior, emotional self-regulation, self-regulation of thought, and physiological self-regulation [49,50].…”
Section: Main Benefits Of Mindfulness In Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different investigations and bibliographic reviews have shown how higher levels of mindfulness improve mental and physical health, and the quality of relationships with others [47,50,51]. In this vein, the literature highlights seven different core processes as the main ones benefiting from mindfulness in business: attention, awareness, cognition, self-regulation of behavior, emotional self-regulation, self-regulation of thought, and physiological self-regulation [49,50].…”
Section: Main Benefits Of Mindfulness In Organizationsmentioning
confidence: 99%
“…Fifth, with regard to the self-regulation of thought, mindfulness allows individuals to observe what is happening (inside and outside) from a more objective point of view, separating the event, thought, or emotions from personal attributions linked to beliefs, memories, learning, or associations. Thus, negative events become less threatening, can be separated from the individual, and consequently do not negatively affect their self-esteem or self-concept [49,51].…”
Section: Main Benefits Of Mindfulness In Organizationsmentioning
confidence: 99%
“…Likewise, a positive relationship was observed between burnout syndrome and stress levels. Very dissimilar results were found by Martínez-Rubio et al [ 49 ], who stated that the practice of physical exercise can reduce stress levels and, therefore, channel burnout syndrome. Physical exercise brings numerous benefits to emotional development, helping to improve mood and attitude when facing tasks [ 6 , 50 ].…”
Section: Discussionmentioning
confidence: 78%
“…Regarding university students, mindfulness can reduce anxiety, depression, and academic stress, even having a protecting role for burnout in healthcare students [59,60]. In this vein, mindfulness-based educational interventions have shown the improvement of the social climate in university classrooms [61].…”
Section: The Role Of Mindfulness In Emotions and Concerns In University Fieldmentioning
confidence: 99%